Effects of Dietary β-Carotene Supplementation on Growth Performance, Biochemical Indices, Hemato-Immunological Parameters, and Physio-Metabolic Responses of the Oriental River Prawn (Macrobrachium nipponense) - Mohammad Ettefaghdoost; Hamid Navirian; Hossein Haghighi (Aquaculture Nutrition)
An 8-week feeding experiment was carried out to determine the influence of β-carotene intake on the growth, biochemical, and immunological responses of Macrobrachium nipponense. Five distinct formulated nutritional regimens were fed to prawns with an average weight of 1.37 ± 0.09 g, each containing varying levels of β-carotene, including 0 (control), 50, 100, 150, and 200 mg/kg. According to the results, the growth metrics were markedly increased by the various levels of β-carotene (p<0.05); however, the hepatosomatic index (HSI) remained statistically unchanged compared to the control treatment (p>0.05). Despite that, a reduction was observed in most hemolymph biochemical indicators, including triglycerides, urea, creatinine, and uric acid (p<0.05). Conversely, high-density lipoprotein (HDL) and low-density lipoprotein (LDL) levels demonstrated a notable increase in comparison to the control group (p<0.05). Moreover, the levels of calcium, phosphorus, and cholesterol did not exhibit any noteworthy differences (p>0.05). The administration of β-carotene resulted in a significant reduction of hemato-immune indices, including lactate dehydrogenase (LDH), aspartate aminotransferase (AST), alanine aminotransferase (ALT), and cortisol (CORT) levels. Conversely, there was a notable increase in the levels of lysozyme (LYZ), albumin (ALB), phenoloxidase (PO), total protein (TP), hyaline cells (HCs), granular cells (GCs), semi-GCs (SGCs), and total hemocyte count (THC) within the β-carotene treatment groups (p<0.05). Furthermore, the majority of the hepatopancreatic antioxidant parameters, including malondialdehyde (MDA), catalase (CAT), and superoxide dismutase (SOD), exhibited a significant decrease in response to β-carotene treatment. However, the total antioxidant capacity (T-AOC) demonstrated a marked increase when compared to the control treatment (p<0.05). Nonetheless, the levels of glutathione peroxidase (GPx) and alkaline phosphatase (AKP) did not exhibit any significant changes by these experimental treatments (p>0.05). The research revealed that elevated dietary levels of β-carotene, specifically at 200 mg/kg, significantly increased digestive enzyme activities, total carotenoid content (TCC), and body chemical composition, including crude protein and crude lipid levels (p<0.05). Despite the β-carotene supplementation, the populations of lactic acid bacteria (LAB) and ash content remained unaffected (p>0.05). Notably, an increase in the levels of β-carotene corresponded with a significant elevation in the expression of genes related to growth and immunity (p<0.05). An elevation in dietary β-carotene significantly increased polyunsaturated fatty acids (PUFAs), monounsaturated fatty acids (MUFAs), and essential amino acids (EAAs) compared to the control group (p<0.05). Eventually, the present research results indicate that the incorporation of 200 mg/kg β-carotene pigment into dietary of the oriental river prawn positively influences the growth indices, hematological, immunological, and metabolic responses of this prawn species.